Keperluan nilai dalam teori Maslow berasaskan puisi kesusasteraan Melayu sekolah menengah - Siti Nurkhalida, Md Ariff (2025)
Literary works play a vital role in educating society, often reflecting human life and its efforts to fulfill psychological, emotional, social, and spiritual needs. Accordingly, this study aims to identify and analyze the human needs portrayed in KOMSAS and KMK poems, while highlighting the importance of values within Maslow’s Hierarchy of Needs as reflected in these literary texts. This study analyzes 130 modern poems featured in Malaysian secondary school textbooks used between the years 2000 and 2020. Employing a qualitative research approach, the study adopts content analysis as its research design, applying Maslow’s Humanistic Theory as the foundational framework for analyzing the selected poems. Maslow identified five fundamental needs that must be fulfilled for an individual to achieve self-actualization, whether in the realms of education, philosophy, psychology, or religion. However, his theory of human needs should be adapted and refined by incorporating Eastern values, making it more relevant and applicable within Eastern societies such as Malaysia. The findings reveal that the KOMSAS and KMK poems analyzed reflect all five levels of needs outlined by Maslow. In addition, the study also highlights the presence of localized values incorporated by the poets to address human needs within the context of the poems. The incorporation of poetry influenced by religious values, moral principles, and local cultural elements is expected to be better understood through the lens of human needs from a value-based perspective. Furthermore, literary analysis is hoped to offer a more holistic interpretation that aligns with local norms and values, thereby enriching the understanding of literary works studied within the educational curriculum